Alumni Engagement And Public Higher Education Institutions Of Pakistan: An Interpretative Phenomenological Analysis - Nisar Pathan, Nabeel (2021)
Over the decades, the landscape of Higher Education (HE) has drastically changed on account of global financial challenges, intense competition, rapidly advancing technology, and unprecedented environmental changes for example, the recent COVID-19 pandemic. As a result, state governments worldwide have consistently decreased their financial support to Public Higher Education Institutions (PHEIs) and required institutions to look for alternate sources of funds. Particularly, PHEIs in developing economies like Pakistan have been severely impacted as the economically struggling federal government has reduced PHEIs’ budget by more than 55 percent in 2020. It is found that to overcome financial challenges, alumni have emerged as the major contributor and most likely potential stakeholder to support institutions in developed economies in monetary and nonmonetary forms. However, institutions in Pakistan have remained unable to capitalize alumni potential to overcome current financial challenge. Thus, lack of alumni support culture in the PHEIs of Pakistan has emerged as an important issue, particularly when questions are raised on the PHEIs long-term financial sustainability. To analyze this issue, this research aimed to understand alumni attitudes towards engagement in the PHEIs of Pakistan through investigating institutional, personal, and environmental influences on alumni attitudes towards engagement